Anticoagulant and antiplatelet combined therapy in patients 75 years and over with atrial fibrillation: a prospective observational study assessing adherence to clinical guidelines. Issue 2 (28th August 2018) - Minary, Anaïs; Michel, Bruno; Gourieux, Bénédicte; Vogel, Thomas
Abstract : Objective: According to current guidelines on atrial fibrillation (AF), the addition of an antiplatelet therapy to an anticoagulant for a stable vascular disease does not decrease the ischaemic hazard but increases the risk of bleeding. The aim of the study was to assess compliance of practices with existing clinical guidelines concerning the use of anticoagulant-antiplatelet combined therapy in patients 75 years and over with AF. Methods: This prospective observational study was carried out at the University Hospital of Strasbourg (France) between August 2016 and January 2017 with data collection on 1 day of every month. To be included, the patient had to be 75 years and over with AF and treated with anticoagulant-antiplatelet therapy. The population included all the patients admitted at the hospital excluding those from the Gynaecology-Obstetrics and Paediatrics departments. With regard to clinical ongoing guidelines (French, European, American and Canadian), the patients were sorted into three groups. Group 1: combined therapy in compliance with recommendations; Group 2: combined therapy debatable as to benefit-risk ratio; and Group 3: combined therapy not compliant with recommendations. Result: Ninety-three out of 3307 patients 75 years and over received anticoagulant-antiplatelet combined therapy prior to their hospital admission. Thirty-two patients (34.4% – Group 1) had experienced an acute event and/or revascularisation within the past year. Twenty-four patients (25.8% – Group 2) had not experienced recent revascularisation and had stable coronary disease but were suffering from peripheral artery disease. Group 3 consisted of 37 patients (39.8%), none of which had experienced recent revascularisation or had unstable coronary disease. For all groups, the main dual therapy was acetylsalicylic acid + fluindione (59.1%). Conclusion: In our study, 37 antiplatelet (39.8%) treatments could have been stopped. These results should spur prescribers into regular reassessment of combination antithrombotic therapy since it contributes to polypharmacy and increases the risk of adverse events.